2018
DOI: 10.1097/lgt.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of High-Grade Cervical Dysplasia in High-Risk Young Women With Low-Grade Cervical Cytology

Abstract: High prevalence of CIN 2/3 in young women with low-grade cervical cytology in this population suggests that it may be prudent to consider alternative surveillance such as colposcopy in similar high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
5
0
3
Order By: Relevance
“…Some authors have found progression rates for CIN 1, CIN 2, and CIN 3 of 5%, 10%, and 12%, respectively . Daily et al observed a high rate of histological CIN 2 or CIN 3 in a group of high‐risk patients with low‐grade cytological dysplasia (19.1%) . Herbert et al also found an increased rate of CIN 3 in women aged 20‐24 years despite falling screening coverage .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have found progression rates for CIN 1, CIN 2, and CIN 3 of 5%, 10%, and 12%, respectively . Daily et al observed a high rate of histological CIN 2 or CIN 3 in a group of high‐risk patients with low‐grade cytological dysplasia (19.1%) . Herbert et al also found an increased rate of CIN 3 in women aged 20‐24 years despite falling screening coverage .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown that sexual activity begins earlier in some populations, and this could lead to an earlier development of high‐grade lesions in younger patients . Daily et al highlighted that this age limit is based on studies of insured patients with excellent access to health care, and its implementation in developing countries or high‐risk populations should be evaluated . Other authors, however, state that lowering the minimum age for screening could lead to overtreatment with untoward effects .…”
Section: Discussionmentioning
confidence: 99%
“…The change in clinical practice pattern and selective colposcopy examination has led to a decrease of follow‐up rates in women with ASC‐US/hrHPV+ since 2013 and provides a possible explanation for the higher detection rates among women aged <25 years who undergo testing with the Cervista and Aptima platforms. Recent studies have found a high prevalence of CIN2/3 in women aged 21‐24 years with ASC‐US cytology and have suggested that it may be prudent to consider alternative surveillance, such as colposcopy, in similar high‐risk populations 32,33 . In addition, a large‐scale study of ASC‐US in the Chinese population showed that the rate of hrHPV positivity decreased with increasing age and was highest in women aged <20 years 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The study characteristics are shown in Table 1. Of the 21 studies about smoking as a risk factor for CIN, nine were crosssectional studies that included between 266 and 12,048 respondents [17][18][19][20][21][22][23][24][25]. Three cross-sectional studies had a different study objective than examining the relationship between smoking and CIN [23][24][25].…”
Section: Study Characteristicsmentioning
confidence: 99%